The oak inside the acorn - Lucado, Max.; Angelini, George, 1951- (Nashville, Tenn. : Tommy Nelson, 2011)
A tiny acorn fulfills its destiny by becoming the tree God made it to be, and then it watches the little girl who climbs its branches grow up as well.
Keywords: Growth -- Fiction; Acorns -- Fiction; Oak -- Fiction; Christian life -- Fiction; Growth -- Juvenile fiction; Acorns -- Juvenile fiction; Oak -- Juvenile fiction; Christian life -- Juvenile fiction; Juvenile works